Faktor berhubungan dengan karies pada pasien asd usia 6-12 tahun - Nathalie, Felicia Kaylila; Dwimega, Arianne (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: Caries is a problem that is most often found in children and adults. Children with Autism Spectrum Disorder (ASD) have various obstacles both in their skills and in their cognition, which makes maintaining their oral hygiene very difficult. Objective: To determine the factors associated with dental caries in patients with ASD aged 6-12 years. Method: Scoping review using journals published in the last 10 years which can be accessed through Google Scholar and Pubmed databases using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. Results: Both databases obtained 421 journals. Duplication filtering found 17 journals with the same title. Filtering titles that do not match the research topic leaves 365 journals. Journal screening through abstracts resulted in 40 journals. All journals were then screened for eligibility leaving 16 journals that met the criteria. Conclusion: Autism Spectrum Disorder (ASD) provides many factors that can cause caries in children aged 6-12 years. Conditions experienced by children with ASD, such as limited motor movements, cognitive problems, eating patterns, oral cavity conditions, and limited access to health services, cause caries in children with ASD.